Status and Rehabilittion Pattern of Mangrove Ecosystem in the Eastern of Segara Anakan Cilacap - Endang Hilmi; Lilik Kartika Sari; Arif Mahdiana; Sesilia Rani Samudra (Jurnal READ (Research of Empowerment and Development), 2020)
The Segara Ankan Lagoon (SAL) has a potentially reduced mangrove ecosystem. In this year, the mangrove area in SAL is predicted only remaining 1788 ha. The degradation of The Segara Ankan Lagoon (SAL) has a potentially reduced mangrove ecosystem. In this year, the mangrove area in SAL is predicted only remaining 1788 ha. The degradation of mangrove ecosystem often occurres in SAL, especially in Eastern of Segara Anakan Lagoon Cilacap (E-SAL). To reduce mangrove degradation need activities to review their status and recovery activities. This research aims to analysis the activities to support the effort of mangrove rehabilitation. The results of this researchd showed that (1) The potential of mangrove ecosystem in E-SAL was seedling between 15.000 – 34.999 trees ha-1, sapling between 5.199-9.065 trees ha-1 and trees between 533 – 1366 trees ha-1, (2) The status of mangrove ecosystem in E-SAL was damaged – very damaged. (3) the model spesices selection of rehabilitation pattern to reduce mangrove degradation were Rhizophora apiculata, Rhizophora mucronata, Aegiceras corniculatum, Sonneratia alba, Avicennia marina, and Bruguiera gymnorrhiza